Candidate sex, partisanship and electoral context in Australia. (April 2021) - Kang, Woo Chang; Sheppard, Jill; Snagovsky, Feodor; Biddle, Nicholas
Abstract: Research on the effect of candidate sex on vote choice has tended to find that, even when voters state preferences for candidates of their own sex, party identification tends to win out on election day. However, not all elections present a clear partisan choice for voters: primary elections in the United States, intra-party candidate selection in Australia, and municipal elections in a range of jurisdictions either pit intra-party candidates against each other or provide only weak partisan cues. In this paper, we use a conjoint experiment to directly compare the effects of candidate sex and partisan affiliation on voters' preferences: in one context where partisan affiliation is constant (e.g. a primary contest) and a second where partisan affiliation varies (e.g. a general election). From a probability-based sample of Australian voters, we find left-identifying female respondents tend to prefer female candidates regardless of the candidate's partisan affiliation and electoral context. By contrast, right-identifying male voters prefer male over female candidates in intra-party contests between right-affiliated candidates, suggesting that conservative men are the least supportive of female candidates. As conservative men dominate Australia's current governing parties, we argue the preferences of this demographic inhibits the advancement of female politicians.